TGF-β blocking combined with photothermal therapy promote tumor targeted migration and long-term antitumor activity of CAR-T cells - Yuxiang Tang; WeiQi Yao; Hang Hu; Wei Xiong; Heng Mei; Yu Hu (Materials Today Bio, 2023)
TGF-β is widely existed in tumor microenvironment, taking part in tumorigenesis process including angiogenesis, cancer associated fibroblast (CAF) proliferation, and immunosuppression. It inhibited the activation, proliferation, migration and differentiation of T cells, in which way caused a limited therapeutic effects of chimeric antigen receptor T (CAR-T) towards solid tumor such as lymphoma. To targeted block TGF-β at tumor site, we take advantages of nano-techniques to deliver TGF-β inhibitors LY2157299 (LY) towards the tumor sites, in order to help achieve a improved and long-term functions of CAR-T towards lymphoma. Based on amphipathic hydroxyethyl starch-polycaprolactone (HES-PCL), LY and photosensitizer indocyanine green (ICG) were co-loaded in HES-PCL to achieve LY/ICG@HES-PCL nanoparticle. The enhanced function of CAR-T benefited from LY/ICG@HES-PCL were verified through lymphoma Raji cells in vitro and Nod scid gamma mice engrafted with the Raji cells in vivo. LY was targeted transported to tumor site and accelerated release by mild ICG photothermal. Chemokines CXCL9/10/11 ​at the tumor site relevant to CAR-T migration and chemokines receptor CXCR3 of CAR-T could be up-regulated by LY, thus facilitated the enhanced accumulation of CAR-T at lymphoma site. T effector memory cells differentiation could also be accelerated by LY/ICG@HES-PCL. Combined therapy of LY/ICG@HES-PCL and CAR-T achieved 2.4 times higher antitumor activity and 2.7 times higher relapse inhibiting rates than CAR-T alone within 15 days and 11 days, respectively. The results suggested that LY/ICG@HES-PCL facilitated the enhanced therapeutic index of CAR-T cells towards lymphoma simply and safely, it may be further potentiated applied for other solid tumors.